Genetic Overlap Between Type 2 Diabetes and Depression in a Sri Lankan Population Twin Sample. Issue 2 (February 2020) - Kan, Carol; Jayaweera, Kaushalya; Adikari, Anushka; Siribaddana, Sisira; Zavos, Helena M.S.; Harber-Aschan, Lisa; Sumathipala, Athula; Hotopf, Matthew; Ismail, Khalida; Rijsdijk, Frühling
ABSTRACT: Objective: Results from twin studies examining the genetic overlap between type 2 diabetes and depression are currently inconclusive. This question has not been addressed in non-Western populations. We aimed to examine whether there are common genetic factors between type 2 diabetes and depression in a Sri Lankan population using genetic model-fitting analysis. Method: The Colombo Twin and Singleton Study–Phase 2 consists of 2019 singletons, and 842 monozygotic and 578 dizygotic twin pairs. The primary outcomes were self-reported type 2 diabetes diagnosis and Beck Depression Inventory scores. Standard bivariate twin models were fitted to estimate the genetic and environmental (co)variance of type 2 diabetes and depression. Results: In the best-fitting model, the phenotypic correlation between type 2 diabetes and depression was significant in female individuals only ( r = 0.15 [0.08–0.21]). This association was primarily attributed to a significant genetic correlation between the traits (rA = 0.53 [0.19–0.98]). Conclusions: In female individuals, but not male individuals, we found a significant genetic overlap between type 2 diabetes and depression in the context of a modest phenotypic correlation.